1130. Optimizing Use of COVID-19 Personal Protective Equipment among Resident Physicians at a Veterans Affairs Hospital. (31st December 2020) - Beaulieu, Ronald M; Kimball, Joanna; Bailin, Samuel S; Lowry, Michael; Werthman, Jennifer A; Gettler, Erin; Gorsline, Chelsea; Lumpkins, Kelly; Ni, Bin; Volpe, Karen; Harris, Bryan; Hulgan, Todd; et al.
Abstract: Background: Correct personal protective equipment (PPE) use is key to prevent infection. Observations on a single unit at the Veterans Affairs (VA) Tennessee Valley Healthcare System (TVHS) prior to COVID-19 (October 2019-February 2020) showed low rates of correct PPE use among healthcare workers (HCWs) (Figure 1). In response to the COVID-19 epidemic, the VA implemented new PPE protocols. Based on our initial observations, we were concerned that incorrect use of PPE may increase the risk of COVID-19 exposure among HCWs. Resident physicians, who work at many sites, may be at high-risk for incorrect PPE use due to rapid turnover and limited site-specific PPE training. We aimed to assess and improve COVID-19 PPE use among internal medicine residents rotating at the VA TVHS. Figure 1: Pre-COVID-19 Observations of Adherence to Contact Precaution Protocols at the Veterans Affairs Tennessee Valley Healthcare System Methods: We used the plan, do, study, act (PDSA) model. Prior to starting VA rotations, residents were emailed PPE education to review. We implemented a 1-hour video conference PPE protocol review at rotation start followed by in-person PPE use evaluations for residents performed by infectious diseases fellows on day 2 and day 5-6 post-review to provide just-in-time educational intervention. Errors at each PPE don/doff step were tracked. Correct PPE use data from both observations were compared using McNemar's test. Baseline and post-implementation resident surveys assessed PPE use knowledge and comfort. Results: Pre-implementation survey response rate was 72% (21/29); 19/21(91%) reported knowing which PPE to use and 16/21(76%) reported knowing how to safely don/doff PPE. Twenty of 29 (69%) residents completed both observations. Errors decreased by 55% (p=0.0045) from 17/20 (85%) to 6/20 (30%) between initial and follow up observations. Errors in hand hygiene, inclusion of all donning/doffing steps, and PPE reuse decreased, but PPE don/doff order errors increased (Figure 2). Post-project survey response rate was 16/29 (55%). All 16 reported knowing which PPE to use and how to safely don/doff PPE, and 11/16 (69%) residents felt both online and in-person interventions were helpful. Figure 2: COVID-19 PPE Errors and Correction Types by Observation Conclusion: Correct COVID-19 PPE use is essential to protect HCWs and patients. Just-in-time education intervention for PPE training may yield higher correct use compared to pre-recorded or online training. Disclosures: All Authors : No reported disclosures